The Influence of Midwife Counseling on Exclusive Breastfeeding on the Knowledge and Practice of Breastfeeding Mothers - Diyan Wahyuningsih (CV. Get Press Indonesia, 2024)
Exclusive breastfeeding plays an important role in supporting optimal growth and development of infants and reducing infant mortality and morbidity. However, the level of exclusive breastfeeding is still low in various regions, including in Padang, one of which is due to the lack of knowledge and practice of breastfeeding mothers. Objective: to determine the influence of midwife counseling on exclusive breastfeeding on the knowledge and practice of breastfeeding mothers in Posyandu Kelurahan Anduring Padang in 2024. Method: this study uses a pre-experimental design with one group pretest-posttest design approach. The sample consisted of 30 breastfeeding mothers who had babies aged 0-6 months, selected by purposive sampling technique. The instruments used were knowledge questionnaires and breastfeeding practice observation sheets. Data were analyzed using paired sample t-test with significance level of 0.05. Result: there was a significant increase in knowledge and practice of breastfeeding mothers after midwife counseling on exclusive breastfeeding (p < 0.05). This shows that counseling is effective in improving the understanding and skills of nursing mothers. Implications: this study is the basis for midwives to strengthen continuing education programs in posyandu. Conclusion: midwife counseling has a significant effect on improving the knowledge and practice of breastfeeding mothers, so that improving the quality and frequency of counseling is expected to expand the scope of exclusive breastfeeding in the community.